The Trypanosomatid Pr77-hallmark contains a downstream core promoter element essential for transcription activity of the Trypanosoma cruzi L1Tc retrotransposon - Macías, Francisco (BMC Genomics, 2016)
BACKGROUND: Trypanosomatid genomes are highly colonized by non-LTR retroelements that make up to 5 % of the nuclear genome. These elements are mainly accumulated in the strand switch regions (SSRs) where polycistronic transcription is initiated and have a 77 nt-long sequence - Pr77 - at their 5′ ends. L1Tc is the best represented retrotransposon in the Trypanosoma cruzi genome and is a potentially functional autonomous element that encodes its own retrotransposition machinery. The Pr77 of the T. cruzi L1Tc element activates gene transcription via RNA polymerase II, generating abundant, unspliced transcripts which are translated. RESULTS: The present manuscript describes the identification of a downstream core promoter element (DPE) in the L1Tc Pr77 sequence. Just four nucleotides long (CGTG), it covers in Pr77 positions +25 to +28 of the described L1Tc transcription start site. The Pr77-DPE motif is conserved in terms of sequence composition and position in the Pr77 of most trypanosomatid non-LTR retrotransposons, independent of the coding or non-coding capacity of these retroelements. Transcription assays in T. cruzi stable transfectants with vector containing point mutations at 17 locations of the Pr77 nucleotide sequence evidence that the DPE motif is essential for the promoter function of Pr77. Furthermore, the obtained data show that other nucleotides also contributed to the promoter function of Pr77. In addition, the presented results indicate that parasite nuclear proteins specifically bind to different regions of the Pr77 sequence although the strongest binding is to the DPE motif. Moreover, it is shown that the DPE sense single-stranded sequence is being required in DNA-protein recognition of nuclear factors. CONCLUSIONS: The Pr77 sequence present in most of non-LTR retrotransposons of trypanosomatids contains a downstream core promoter element (DPE) which is conserved in terms of nucleotide composition and location. The Pr77-DPE motif is essential for the transcriptional activity of Pr77 although other nucleotides are also involved. DPE has a high affinity binding for nuclear proteins in T. cruzi. The wide retroelement-mediated distribution of Pr77 suggests that it may represent an important tool for regulating gene expression in trypanosomatids. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2427-6) contains supplementary material, which is available to authorized users.